Band Alignment Engineering in Two‐Dimensional Transition Metal Dichalcogenide‐Based Heterostructures for Photodetectors. Issue 3 (21st December 2020) - Liu, Ran; Wang, Fakun; Liu, Lixin; He, Xiaoyu; Chen, Jiazhen; Li, Yuan; Zhai, Tianyou
Abstract : The hybridization of two‐dimensional transition metal dichalcogenides (2D TMDs) with other light‐sensitive materials to fabricate the TMD‐based heterostructures is an effective way to boost the overall photoelectric performance of photodetectors. In particular, the alignment of band structure at the interface of the binding materials plays a critical role in optimizing the carrier transfer path and prompting the charge separation rate, which finally lead to the simultaneous improvement of photoresponsivity and response rate and the expansion of detection range. However, the band alignment engineering topic has been barely summarized and reviewed in detail up to today. Herein, a specific review focused on the band alignment strategies and the related charge‐transfer mechanism of the recently developed novel TMD heterostructures for photodetectors is provided. The band structures are classified into four categories according to the targeted function of photodetectors, including that formed by TMDs with zero‐bandgap materials, narrow‐bandgap semiconductors, middle‐bandgap semiconductors, and wide‐bandgap semiconductors. The corresponding band alignment principles and charge‐transfer behaviors are summarized carefully by providing various latest research works as representative examples under each category. Herein, a key reference for applying and extending the fundamental band alignment principles in the design and fabrication of future TMD‐based heterostructural photodetectors is provided. Abstract : The band structure alignment at the heterostructural interface of 2D TMD‐based photodetectors plays a critical role in optimizing the carrier transfer path and prompting the charge separation rate. Herien, a specific review focused on the band alignment strategies and the related charge‐transfer mechanism of the recently developed novel TMD heterostructures for photodetectors is provided.